Pengembangan Masyarakat Berbasis Keagamaan melalui Majelis Taklim “Ngaji Urip” di Tanjungrejo, Margoyoso, Pati - Setiawan, Aris; Aksa, Ahmad Habiburrohman (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2025)
This study examines the role of the “Ngaji Urip” Taklim Council in religious-based community development in Tanjungrejo Village, Margoyoso District, Pati Regency. The research aims to analyze the council’s contribution as a vehicle for social transformation through spiritual and local wisdom approaches. A qualitative method was employed, with data collected through participatory observation, in-depth interviews, and documentation studies. The results indicate that “Ngaji Urip” successfully integrates religious values with community development across four dimensions: (1) social, by strengthening solidarity and forming farmer groups; (2) economic, through entrepreneurial initiatives such as organic fertilizer production; (3) cultural, by revitalizing local traditions via the Muria Raya Festival; and (4) personal and spiritual, through enhanced life awareness and moral character. The program’s impacts include community empowerment, cultural preservation, and locally-based economic growth. The study concludes that religious-based approaches can offer holistic solutions to modernization challenges, such as social inequality and moral degradation. Further research is recommended to explore replicating this model in different contexts and assessing its long-term effects.